Effect of Electrolyte Concentration on Electrochemical Performance of Bush Like α‐Fe2O3 Nanostructures. Issue 37 (1st October 2021) - Yasnur, Sk; Saha, Samik; Ray, Apurba; Das, Mahimaranjan; Mukherjee, Ayan; Das, Sachindranath
Abstract: The nano‐sized bush‐like α‐Fe2 O3 particles were synthesized using sol‐gel auto combustion route. The structural characterization of obtained α‐Fe2 O3 was performed by X‐ray diffraction (XRD) method to confirm its phase and crystallinity. The Scanning Electron Microscopy (SEM) confirmed the formation of bush‐like nanostructure which was further used for the electrochemical charge storage performance testing. The electrochemical performances of the synthesized electrode material were studied by using Cyclic Voltammetry (CV) and electrochemical impedance spectroscopy (EIS) analysis in a three electrode configuration. The variation of specific capacitance values with the different molar concentration of electrolyte has been discussed. An enhancement in the specific capacitance has been observed up to 3 M KOH electrolyte solution. The maximum value of specific capacitance is 202.2 F g −1 which is obtained at a scan rate of 2 mV s −1 for 3 M aqueous KOH solution as electrolyte. Abstract : The bush‐like α‐Fe2 O3 nano‐structure were obtained using sol‐gel auto combustion route. The Rietveld method applied on XRD data whereas SEM confirmed its morphology. The electrochemical measurement within 1–4 moles KOH electrolytes was done in a three electrode configuration. A high of specific capacitance is 202.2 F g −1 was obtained at potential scan rate of 2 mV s −1 for 3 M aqueous KOH electrolyte solution. The variation of specific capacitance values with the different molar concentration of electrolyte has been discussed.